Pendampingan Pembuatan dan Fungsionalisasi Website Sebagai Media Pembelajaran Lintas Agama di SMP Buntut Bali Katingan - Muslimah Muslimah; Isabella Jeniva; Anak Agung Gede Wiranata; Salsabila Rizky Amalia; Rikhsan Aprilinandra; Salsabiela Putri Widodo; Jarina Jarina; Sintani G.; Guent Stepania; Nasa Garuda; Della Kristina; Tuti Yuniati; Kasih Kasih; Jansen Mutchell Fernando Zacharias; Rizqiyah Nihayatun Nufus; Zacharias Zacharias (GUYUB: Journal of Community Engagement, 2024)
Adapting to technological advancements is a necessity; however, not all schools have the necessary resources, and not all teachers and students are proficient in using them, including those at SMP Negeri 1 Buntut Bali in Katingan Regency. Therefore, it is crucial for students from the National KKN (Community Service Program) on Religious Moderation to assist in the creation and functionalization of a website at SMP Negeri 1 Buntut Bali, where the teachers and students practice Islam, Christianity, and Hinduism, to help maintain and strengthen religious moderation in Buntut Bali village. The service approach used is the Participatory Action Research (PAR) model, involving the community selected through purposive sampling, including all teachers and students at SMP Negeri 1 Buntut Bali. The results of this service during the mentoring of the school's website creation, named EAR.COM (Educated and Religious), have been greatly beneficial to the school. To ensure the website's continued functionality, the facilitators conducted training for all teachers of different religions at SMPN 1 Desa Buntut Bali on using the website to develop materials by adding images, videos, and other content. The website was designed to be simple and easily accessible by students and can be used flexibly as it can be accessed even outside the school, making it easier for teachers to guide students in its use. This has enabled both teachers and students to deepen their understanding of religious moderation through the available materials on the website.